A cultura popular da literatura de cordel no estudo dos fenômenos óticos em nível de ensino médio - Araújo, Francisco Vanderli de (Universidade Federal Rural do Semi-Árido, 2019)
This research shows the application of twine leaflets in the teaching of physics. One must escape the traditionalism of teaching that is still used in classrooms and show new tools to make learning more effective, thus, leaflets will be used as a tool for teaching physics. This work has as general objective, to show the cordel literature tool applied in physics teaching, at the high school level, and to verify if its use can improve the learning of students in the Physics discipline, specifically in the geometrical optics contents. In this research, we used Lev Vygotsky's theory of mediating learning, where students (central subjects of learning) studied the twine, and through debates discussed the physics present in them, in this theory the students are the protagonists and the teacher is only a mediator of the process. Twine leaflets were applied on geometric optics contents (Initial Optical Concepts, Flat Mirrors and Reflection Laws, Spherical Mirrors and Optical Instruments). The students' speeches were used during the classes and in a final interview to understand, qualitatively, the use of this tool and the assimilation of the knowledge of Physics present in the pamphlets that were made on the theme of geometric optics and applied in the 2nd grade. a public school in the state of Ceará. With the application of the leaflets in physics classes, we get great results in understanding the contents. Due to the above mentioned facts, it is clear that the cordel literature tool can be applied in the teaching of physics and can lead students to learning success.
Keywords: Ensino de física; Óptica geométrica; Folhetos de Cordel; Physics teaching; Geometric optics; Cord Flyers; CIENCIAS EXATAS E DA TERRA::FISICA